Do usage counts of scientific data make sense? An investigation of the Dryad repository. Issue 2 (19th June 2017) - He, Lin; Han, Zhengbiao
Abstract : Purpose: The purpose of this paper is to evaluate the impact of scientific data in order to assess the reliability of data to support data curation, to establish trust between researchers to support reuse of digital data and encourage researchers to share more data. Design/methodology/approach: The authors compared the correlations between usage counts of associated data in Dryad and citation counts of articles in Web of Science in different subject areas in order to assess the possibility of using altmetric indicators to evaluate scientific data. Findings: There are high positive correlations between usage counts of data and citation counts of associated articles. The citation counts of article's shared data are higher than the average citation counts in most of the subject areas examined by the authors. Practical implications: The paper suggests that usage counts of data could be potentially used to evaluate scholarly impact of scientific data, especially for those subject areas without special data repositories. Originality/value: The study examines the possibility to use usage counts to evaluate the impact of scientific data in a generic repository Dryad by different subject categories.